Perlindungan Hukum bagi Pegawai Pemerintah dengan Perjanjian Kerja (PPPK) Paruh Waktu dalam Sistem Kepegawaian di Indonesia - Yik Soleh Assegaf; Widhi Chayo Nugroho (Media Hukum Indonesia (MHI), 2026)
This study aims to analyze the legal protection provided for part-time Government Employees with Work Agreements (PPPK) within Indonesia’s civil service system, using a literature-based research approach. Part-time PPPK personnel represent an emerging category of government workers aligned with the growing need for flexible work arrangements in public service delivery. However, their contract-based employment status often places them in a less secure position compared to permanent civil servants. Through the review of statutory documents, academic literature, and institutional reports, the study finds that legal protection for part-time PPPK employees is generally recognized through principles of non-discrimination, legal certainty in employment relations, and the guarantee of basic rights such as fair remuneration, social protection, and safe working conditions. Despite these formal provisions, regulatory gaps remain, particularly in the areas of workload arrangements, performance evaluation systems, contract renewal mechanisms, and access to dispute resolution within the civil service framework. Variations in implementation among government institutions further contribute to uncertainty faced by part-time PPPK workers. This study highlights the need for regulatory harmonization and the development of more detailed technical guidelines to ensure equal protection between part-time PPPK employees and other categories within the national civil service system. Strengthening these mechanisms would not only enhance legal clarity but also support sustainable and efficient public service delivery through a well-protected contractual workforce.